An experimental application on denim garment to give thermal regulation property - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2017)
In this context, the influence of phase change material (PCM) finishing on denim jeans' on thermal regulation and other selected properties was investigated. Denim garments were treated with microcapsulated PCM in various concentrations given in bath and by dipping, followed by the curing process. Differential scanning calorimeter tests were applied to denim fabrics. Morphology of microcapsules was characterized by scanning electron microscopy analyses and color analyses of the garments were done and evaluated.
Keywords: Phase change materials; denim; thermal regulation; DSC; microencapsulation; PHASE-CHANGE MATERIALS; TEXTILES; FABRICS